Effects of Duhuo Jisheng Decoction on Calcium Homeostasis and Apoptosis of Chondrocytes under Endoplasmic Reticulum Stress - Qing LIN; Wenyi WANG; Danhong PAN; Yanfeng HUANG; Changlong FU; Jinxia YE (康复学报)
Objective:To observe the effect of Duhuo Jisheng decoction on the balance of calcium homeostasis and apoptosis of chondrocytes under endoplasmic reticulum stress(ERS), and to preliminarily explore its mechanism of preventing and treating osteoarthritis.Methods:A steady chondrocyte in vitro culture system was established by using 4-week-old SD rat knee cartilage, and identify the third generation chondrocyte by toluidine blue staining.The 25 μmol/L Thapsigargin(TG)was used to induce chondrocyte in vitro culture to produce endoplasmic reticulum stress(ERS), incubate it in Duhuo Jisheng Decoction(100, 200, 400 μg/mL)for 24 hours after induction.The cells were divided into the blank group, the model group, the low-dose Duhuo Jisheng decoction group, the medium-dose Duhuo Jisheng decoction group, and the high-dose Duhuo Jisheng decoction group.Then morphological changes of chondrocytes were observed respectively by inverted microscope, viability of chondrocyte in each group was examined by CCK-8 method, chondrocyte apoptosis was observed by Hoechst 33342 staining and real-time dynamic changes of intracellular Ca2+concentration was examined by double turntable laser confocal microscope.Results:①The morphology of chondrocytes: the cells in the blank group grew in a single-layer paving stone shape, while the cells in the model group increased in a polygonal shape, the pseudopodia increased, the gaps widened, and the number of cells decreased significantly.Compared with the model group, the number of cells in the three dose groups of Duhuo Jisheng decoction(100, 200, 400 μg/mL)increased significantly and the cytoplasm was uniform.The activity of chondrocytes in each group: compared with the blank group, the survival rate of the model group was lower, and the difference was statistically significant(P<0.05).The absorbance of each concentration group of Duhuo Jisheng decoction increased with the increase of concentration, and the difference was statistically significant compared with the model group(P<0.05).③Apoptosis of chondrocytes: the number of apoptosis in the model group was significantly increased, and the degree of pyknosis of the nucleus was obvious, and some of them were a high density of bright blue or half moon-shaped.The number of apoptotic cells in each dose group of Duhuo Jisheng decoction was significantly reduced, only a few apoptotic cells showed a high density of bright blue or half-moon shape, and the number of apoptosis decreased with the increase of the concentration of Duhuo Jisheng decoction, showing a certain dose-effect relationship.④The changes of intracellular calcium ion concentration: the calcium ion fluorescence intensity of the cells in the blank group was weaker and more uniform, maintaining a stable state.The calcium ion release of the model group was significantly increased, and the fluorescence intensity was enhanced.The fluorescence spectrum showed that calcium sparks were more frequent.Compared with the blank group, the difference was statistically significant(P<0.05).Chondrocytes in the medium and high-dose Duhuo Jisheng decoction groups could quickly return to calcium homeostasis, and calcium sparks were significantly reduced.Although there were still some calcium sparks in the low-concentration Duhuo Jisheng decoction group, the fluorescence intensity was significantly weaker than the model group.Conclusion:Duhuo Jisheng decoction has an inhibitory effect on the apoptosis of chondrocyte induced by TG, the mechanism may be that Duhuo Jisheng decoction can alleviate endoplasmic reticulum stress by regulating calcium balance, thus inhibiting the apoptosis of chondrocyte.